Advocacy and Justice in the Digital Era: Contemporary Challenges and Innovations in Indonesian Legal Services - Aprila Niravita; Asmarani Ramli; Windiahsari Windiahsari; Muhammad Adymas Hikal Fikri (Indonesian Journal of Advocacy and Legal Services, 2026)
This editorial introduces the key themes in the Indonesian Journal of Advocacy and Legal Services Volume 8 Issue 1 (2026), titled "Legal Advocacy and Justice Innovation." The ten articles in this edition examine diverse topics including civic education and legal literacy, consumer protection in digital transactions, anti-bullying education, comparative antitrust law, labor rights for home-based workers, data protection in AI chatbots, constitutional election reform, legal aid effectiveness, university legal documentation governance, and state-owned enterprise transformation. Drawing on case studies from Indonesia, Malaysia, Singapore, Uzbekistan, Russia, the Netherlands, the European Union, Japan, Estonia, Australia, the United Kingdom, India, and South Africa, the issue provides comparative insights into evolving legal practices across multiple jurisdictions. The edition highlights persistent challenges such as unequal access to justice, regulatory fragmentation, governance deficits, and the tension between technological innovation and legal protection. Emphasizing interdisciplinary and socio-legal approaches, this edition contributes to advancing advocacy as a tool for legal empowerment, institutional reform, and social justice in Indonesia's rapidly transforming legal landscape.